Dependent seniors A.D. 2035 - new sources of support - Szweda-Lewandowska, Zofia (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In 2014 years - according to the Central Statistical Office - the percentage of people aged 60 and more, reached 21.5%, and already in 2040 every third person will be 60 years or more. The majority of nations, including Poland, face the problem of population ageing. Therefore, providing care for elderly persons is crucial. A decline in the care-giving potential of families and the rapid increase in the percentage of senior citizens make it necessary to develop different sources of assistance designed for the elderly. The aim of this paper is to estimate the demand for care services and the possible sources of support.